Application of Fuzzy C-Means Algorithm in Grouping Population Status in Nanjungan Village - Ardiansyah, Sohenra; Sari , Herlina Latipa; Sartika , Devi (Jurnal Komputer, 2022)
Nanjungan Village is one of the villages in Semidang Alas District, Seluma Regency, Bengkulu Province. Every year, the Nanjungan Village Office collects population data within the scope of Nanjungan Alas Village in order to find out the underprivileged population in the village. However, the processing of population data is still done manually by surveying each resident and providing an assessment. The application of the Fuzzy C-Means algorithm in grouping population status in Nanjungan Village can help manage population data and can also help provide recommendations in the form of information on the results of grouping population status data which is divided into 2 groups, namely the less fortunate and the less fortunate. Based on the results of the tests that have been carried out by applying the Fuzzy C-Means Algorithm through observational data in 2021, totaling 618 residents in Nanjungan Village, 5% of the population is taken so that the data is processed as many as 31 residents, the result is that 51.6 % entered into Cluster C1 (Disabled) and 48.4% entered into Cluster C2 (Poor)